Undetectable plasma viral load predicts normal survival in HIV-2-infected people in a West African village - van der Loeff, Maarten F Schim; Larke, Natasha; Kaye, Steve; Berry, Neil; Ariyoshi, Koya; Alabi, Abraham; van Tienen, Carla; Leligdowicz, Aleksandra; Sarge-Njie, Ramu; da Silva, Zacharias; Jaye, Assan; Ricard, Dominique; et al. (Retrovirology, 2010)
There have been no previous studies of the long-term survival and temporal changes in plasma viral load among HIV-2 infected subjects. 133 HIV-2 infected and 158 HIV-uninfected subjects from a rural area in North-west Guinea-Bissau, West Africa were enrolled into a prospective cohort study in 1991 and followed-up to mid-2009. Data were collected on four occasions during that period on HIV antibodies, CD4% and HIV-2 plasma viral load. Median age (interquartile range [IQR]) of HIV-2 infected subjects at time of enrollment was 47 (36, 60) years, similar to that of HIV-uninfected control subjects, 49 (38, 62) (p = 0.4). Median (IQR) plasma viral load and CD4 percentage were 347 (50, 4,300) copies/ml and 29 (22, 35) respectively.Overall loss to follow-up to assess vital status was small, at 6.7% and 6.3% for HIV-2 infected and uninfected subjects respectively. An additional 17 (12.8%) and 16 (10.1%) of HIV-2 infected and uninfected subjects respectively were censored during follow-up due to infection with HIV-1. The mortality rate per 100 person-years (95% CI) was 4.5 (3.6, 5.8) among HIV-2 infected subjects compared to 2.1 (1.6, 2.9) among HIV-uninfected (age-sex adjusted rate ratio 1.9 (1.3, 2.8, p < 0.001) representing a 2-fold excess mortality rate associated with HIV-2 infection.Viral load measurements were available for 98%, 78%, 77% and 61% HIV-2 infected subjects who were alive and had not become super-infected with HIV-1, in 1991, 1996, 2003 and 2006 respectively. Median plasma viral load (RNA copies per ml) (IQR) did not change significantly over time, being 150 (50, 1,554; n = 77) in 1996, 203 (50, 2,837; n = 47) in 2003 and 171 (50, 497; n = 31) in 2006. Thirty seven percent of HIV-2 subjects had undetectable viraemia (<100 copies/ml) at baseline: strikingly, mortality in this group was similar to that of the general population. A substantial proportion of HIV-2 infected subjects in this cohort have stable plasma viral load, and those with an undetectable viral load (37%) at study entry had a normal survival rate. However, the sequential laboratory findings need to be interpreted with caution given the number of individuals who could not be re-examined.